On Some Classes of Linear Volterra Integral Equations - Anatoly S. Apartsyn (Abstract and Applied Analysis)
The sufficient conditions are obtained for the existence and uniqueness of continuous solution to the linear nonclassical Volterra equation that appears in the integral models of developing systems. The Volterra integral equations of the first kind with piecewise smooth kernels are considered. Illustrative examples are presented.